Effect of severity and incidence levels of crown rust and stem rust on yield of oat genotypes - Caierão, Eduardo; Carvalho, Fernando Irajá Félix de; Floss, Elmar Luiz; Sánchez-Chacón, Carlos Danilo; Lonrecetti, Claudir; Marchioro, Volmir (Pesquisa Agropecuaria Brasileira, 2001)
Germoplasm introduction represents an alternative to increase oat (Avena sativa L.) variability, favoring selection. The objectives of this study were: a) to select oat lines with high grain yield and adaptation to State conditions; b) to determine the relationship between crown and stem rust with grain yield; c) to estimate the relationship between severity and incidence rules as tools to diagnose disease intensity. Fifty seven oat lines were evaluated for grain yield and other characters. The lines were classified using the mean standard deviation and the data was submitted to correlation and regression analyses. Only three introduced lines looked promising. The correlation between crown rust and grain yield was significant, differently from stem rust. Severity to incidence regression of diseases showed quadratic behaviour, although linear relations were observed in low incidence levels. From disease reaction type, the selected lines are valuable to oat breeding programs. Incidence rule can efficiently replace the severity rule at low epidemic levels, facilitating field diagnostics.
Keywords: selection; genotypes; plant diseases; disease resistance; breeding methods